POKŁOSIE OKRĄGŁEGO STOŁU PRZESZŁOŚĆ DLA PRZYSZŁOŚCI - Woźniak, Zbigniew (Wydział Prawa i Administracji UAM, 2009)
The political contract concluded a t the “Round Table” twenty years ago continues to produce much controversy, and when confronted with the subsequent political changes it reveals its sociotechnical and tactical character. The negotiating team representing the Solidarity and opposition consisted largely of city intellectuals with long-time oppositionist history, capable of presenting the existing authorities a different vision of Poland and its society. They also managed to win legalisation of independent trade unions and other social organisations, turn their 35% parliamentary representation into a stronghold from which they continued to attract more followers, both from the Democratic Alliance and Peasant Party, formerly allied to the ruling Workers’ Party, and eventually create grounds for electing the first opposition prime minister. With this accomplished, the economic reforms have accelerated and the political scene has become more diversified. However, there are still reforms th a t need completion before the citizens can be fully integrated to participate actively in the transformation of their own country, and become more interested in public matters. Therefore, in the concluding part of the paper, effects and consequences of the unfinished political transformation are indicated. This is followed by the author’s own concept of a balanced society with integrated citizens.
AFTERMATH OF THE “ROUND TABLE”: THE PAST FOR THE FUTURE